Engagement and flow in the job satisfaction of volunteers at a non-governmental organization (NGO) in Peru - Palomino-Flores, Javier Valentino; Carhuancho-Mendoza, Irma Milagros; Ponce Yactayo, Dora Lourdes; Saravia-Ramos, Giuliana del Pilar; Meleán Romero, Rosana Alejandra; Nolazco-Labajos, Fernando Alexis (Business: Theory and Practice, 2025)
The objective was to analyze how engagement and the state of flow influence the job satisfaction of volunteers. The design was non-experimental, cross-sectional, and the sample consisted of 1023 volunteers, selected through non-probabilistic convenience sampling. Validated questionnaires were used: a) the Utrecht Work Engagement Scale (Schaufeli et al., 2003); b) the Flow Experience Scale (Bakker, 2008); and c) the Job Satisfaction Scale SL-20/23 (Meliá & Peiró, 1998). Reliability was assessed using Cronbach’s alpha. Exploratory and confirmatory factor analyses were conducted. Data were collected and processed using SPSS, AMOS, and SEM. Both flow (0.703) and engagement (0.557) have a significant influence on the job satisfaction of volunteers, with both factors being relevant for improving job satisfaction. The state of flow is a stronger predictor than engagement. It is concluded that there is a significant and positive influence of engagement and flow on the job satisfaction of volunteers. The study of these topics confirms the importance of fostering engagement and flow among volunteers to enhance their job satisfaction.